(untitled) - Crigger, C. K. (Thorndike, Maine, 2023)
"Its hard to deny friends asking for help -- even when it means stepping headlong into danger. As a sort of left- over deputy from a previous adventure, January Billings is compelled to answer the call when a valuable gun is stolen from the local mercantile, and the storekeeper viciously assaulted. The town marshal is out of action and the sheriff is an ineffectual fool. What else can she do but step up? Besides, the stolen gun links Eli Pasco to the situation and she wants to know why. However, old connections dont make the job any easier. To make matters worse, a gang of outlaws -- two of which harbor grudges against January and Eli -- have drifted into town to work a complex investment scam and rob a bank. Death will walk the streets of the little western town on this cold winter night, pitting a few against many. What will it take to beat the odds? The odds are stacked against her, but she likes it that way . . ."--
Keywords: Fiction; Fiction; Frontier and pioneer life; Fiction; Robbery; Fiction; West (U.S.); Policewomen; Outlaws; West (U.S.); Fiction; Large print books; Historical western fiction; Western fiction